2020
DOI: 10.1177/0887302x20973960
|View full text |Cite
|
Sign up to set email alerts
|

Smart Wireless Charging Heating Insoles: Improving Body Thermal Comfort of Young Males in an Extremely Cold Environment

Abstract: Currently, no study was retrieved for scientifically design heating insoles and evaluating their actual effectiveness in improving body thermal comfort of occupational workers in extremely cold environments. To fill this gap, novel smart wireless charging heating insoles (SWHI) were developed, consisting of electrically heating pads targeted at the toe and heel regions. Seven young males were asked to perform twice repeated cycles of 50-min treadmill walking at 4.0 km/h and 20-min standing to simulate the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A preliminary review of the literature has been carried out into trials seeking to evaluate the efficacy of heating e-textiles in cold environments. [4][5][6][7][8][9][10][14][15][16][17][18] Relevant keywords related to heating, textile, and cold environments were identified and preliminary results showed that the common body regions heated by thermal e-textiles are: (a) torso, (b) feet/toes, and (c) more than two regions. To examine thermal wear performance, researchers generally had an experimental group (HEAT) placed in a cold environment and a control group (CON) situated in a thermo-neutral or in a cold environment but wearing unheated clothing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary review of the literature has been carried out into trials seeking to evaluate the efficacy of heating e-textiles in cold environments. [4][5][6][7][8][9][10][14][15][16][17][18] Relevant keywords related to heating, textile, and cold environments were identified and preliminary results showed that the common body regions heated by thermal e-textiles are: (a) torso, (b) feet/toes, and (c) more than two regions. To examine thermal wear performance, researchers generally had an experimental group (HEAT) placed in a cold environment and a control group (CON) situated in a thermo-neutral or in a cold environment but wearing unheated clothing.…”
Section: Methodsmentioning
confidence: 99%
“…11 In some applications temperature can be adjusted automatically with wireless charging which facilitates remote usage. 7 The results of studies illustrate the effectiveness of each textile product in ameliorating human thermal comfort in different situations. In terms of systematic review and meta-analysis, a number of studies have examined personal comfort systems (PCSs) 12 and the effectiveness of cooling garments in minimizing heat strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although tactile stimulation to the plantar may improve gait, it may be technically difficult to change the shape of the insole and create protrusions during walking. In contrast, heat-generating insoles with electrically heated elements embedded in the insole have been developed and marketed in recent years [ 14 , 15 ]. Most are charged by a power supply from USB or other sources and generate heat in response to the ambient temperature (e.g., in cold environments) to maintain a comfortable plantar temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also compared the superiority of planter stretch over stretch of tendon Achilles and the result revealed the stretch of planter fascia is relatively more effective than tendon Achilles stretch in patient of planter fascia. Combination of both stretch (planter fascia stretch and calf stretch) are very effective in resolving the issue, restoring the normal range of motion and decreasing the pressure from stiff and tight planter fascia.But there is no study has identifi ed the independent effi ciency of these exercises [10,11]. Some studies show that non-steroidal anti-infl ammatory drugs in decreasing pain and reducing the infl ammation of planter fascia, but the effi ciency of these drugs in patient with chronic issue still remain obscure [12].…”
Section: Introductionmentioning
confidence: 99%